Portreti visokošolskih učiteljev, zaslužnih za nastanek Medicinske fakultete v Mariboru, ki so bili zaposleni v Splošni bolnišnici Maribor in habilitirani do leta 2002: Tempus fugit / čas beži (University of Maribor Press, 2019)
Portraits of Higher Education Teachers who Deserve Credit for the Formation of the Faculty of Medicine in Maribor and were Employed at the General Hospital Maribor and Habilitated up to the Year 2002: Tempus fugit / Time Passes. The establishment of the Faculty of Medicine of the University of Maribor (MF UM) in the year 2003 would not be possible without numerous higher education teachers from the former General Hospital Maribor (SB MB), the present University Clinical Centre Maribor (UKC MB) who were habilitated up to the year 2002, who visionaryly ploughed ahead with scientific and pedagogical paths in Maribor. This is why the existent book is dedicated exactly to them, for their contribution to the development of health care in Maribor is of remarkable importance. During the years of formation of the faculty we have turned to esteemed and world renowned domestic and foreign experts, top-most professors and academicians who staked their honour and good name on historical project of the formation of the faculty. To the most visible among them we, after the decision of the Senate of the Faculty of Medicine of the University of Maribor, bestowed honorary title Honorary visiting professor of the Faculty of Medicine of the University of Maribor.During the recent past years we have successfully implemented numerous projects: the opening of the Institute for Anatomy, Histology and Embryology, the Institute for Physiology, the Laboratory Centre, the Simulation Centre, the moving of the faculty to the new building on the Tabor embankment. With the new premises we have gained special conditions for pedagogical and research work. Ahead of us there are already new projects: ready are study programmes Dental Medicine, Pharmacy and General Medicine in the English language. These are projects for the present and for the future of the Faculty of Medicine of the University of Maribor. According to the proverb, there is neither present nor future without the past. And the respect for the past is also assurance that we have the future. With this book we would like to express gratitude once again to all our teachers who were active in the General Hospital Maribor and the book will remain as a reminder to our posterity.